Headache and Methemoglobinemia. Issue 1 (14th November 2019) - Khan, Fawad Ahmed; McIntyre, Caley; Khan, Abdul Mukhtadir; Maslov, Alexander
Abstract : Aim: This basic review is intended to summarize the current knowledge of methemoglobinemia as an important cause of secondary headache with the hope of generating a growing interest in studying this phenomenon. Background: We describe the pathological underpinnings of headaches generated by hypoxia. Possible mechanisms include cerebral vasodilation‐associated stretching of the vessel nociceptors, sensitization of perivascular nociceptors mediated by nitric oxide, cerebral calcitonin gene‐related peptide, activation of the cyclic adenosine monophosphate pathway, cortical spreading depression, disruption of the blood‐brain barrier, and neurogenic inflammation. We review the clinical features, pathophysiology, and management of methemoglobinemia. We conducted a literature review of reports of symptomatic methemoglobinemia with headache. In addition, we describe a case report of a patient who presented with an acute onset of severe holocranial headache associated with rapidly progressive perioral paresthesia, cyanosis in lips and hands, nausea, and mild dyspnea on exertion. These features can be misinterpreted as an acute attack of migraine with pain‐related hyperventilation syndrome and anxiety leading to clinically detrimental delay in the management of the progressive hypoxia. Her symptoms resolved following treatment with methylene blue. The complex relationship of migraine and hypoxia‐related headaches is also reviewed. We propose that methemoglobinemia‐associated headaches are possibly generated by stretching of the nociceptor nerve endings during cerebral vasodilation and hypoxia‐mediated oxidative stress. Conclusions: The case highlights the need to broaden the formulated differential diagnosis of an acute onset severe holocranial headache and pay careful attention to other signs and symptoms that may provide hints on potential mechanism(s) for secondary headaches. We provide justification for the need to incorporate "Headache attributed to Methemoglobinemia" as a subtype under the section "Headache attributed to hypoxia and/or hypercapnia" of the International Classification of Headache Disorders to support clinical decision making.